Hypothalamo-pituitary-adrenal axis, glucose metabolism and TNF-α in narcolepsy - Maurovich-Horvat, Eszter; Keckeis, Marietta; Lattová, Zuzana; Kemlink, David; Wetter, Thomas-Christian; Schuld, Andreas; Sonka, Karel; Pollmächer, Thomas (Journal of sleep research, 2014)
Narcolepsy with cataplexy is caused by a deficiency in the production of hypocretin/orexin, which regulates sleep and wakefulness, and also influences appetite, neuroendocrine functions and metabolism. In this case-control study, 11 patients with narcolepsy with cataplexy and 11 healthy adults underwent an oral glucose tolerance test, and dexamethasone suppression/corticotropin-releasing hormone stimulation test. The average age of patients and controls was 35.1 ± 13.2 and 41.0 ± 2.9 years, respectively, body mass index was 28.1 ± 6.6 and 25.5 ± 4.7 kg m(-2) . We did not find evidence of a significantly increased prevalence of disturbed glucose tolerance in patients with narcolepsy. After hypothalamo-pituitary-adrenal axis suppression, the number of non-suppressors did not differ between the groups, indicating normal negative feedback sensitivity. The level of cortisol after dexamethasone suppression was significantly lower in patients with narcolepsy, suggesting a slight basal downregulation and/or a slightly increased negative feedback sensitivity of the major endocrine stress system in narcolepsy. Following corticotropin-releasing hormone stimulation, there were no significant differences in levels of adrenocorticotropic hormone or cortisol, and in adrenocortical responsivity to adrenocorticotropic hormone. Finally, patients with narcolepsy displayed significantly higher plasma levels of tumour necrosis factor alpha, soluble tumour necrosis factor receptor p55, soluble tumour necrosis factor receptor p75 and interleukin 6 after adjustment for body mass index. The present study confirms that narcolepsy by itself is not associated with disturbances of glucose metabolism, but goes along with a subtle dysregulation of inflammatory cytokine production. We also found that dynamic hypothalamo-pituitary-adrenal system response is not altered, whereas negative feedback to dexamethasone might be slightly enhanced.
Keywords: dospělí; adrenokortikotropní hormon; hormon uvolňující kortikotropin; glukózový toleranční test; Female; stress system; Hypothalamo-Hypophyseal System; Adult; Tumor Necrosis Factor-alpha; ženské pohlaví; hydrokortison; lidé; Blood Glucose; Glucose Tolerance Test; Hydrocortisone; Cataplexy; studie případů a kontrol; Interleukin-6; glucose; immune system; systém hypotalamus-hypofýza; Adrenocorticotropic Hormone; kataplexie; TNF-alfa; Male; Case-Control Studies; dexamethason; Dexamethasone; index tělesné hmotnosti; interleukin-6; narkolepsie; systém hypofýza - nadledviny; cytokines; Narcolepsy; Pituitary-Adrenal System; mužské pohlaví; Body Mass Index; krevní glukóza; Corticotropin-Releasing Hormone; metabolism; Humans